Neuropsychological presentation and adaptive skills in high-functioning adolescents with visual impairment: A preliminary investigation. Issue 2 (3rd April 2017) - Greenaway, R.; Pring, L.; Schepers, A.; Isaacs, D. P.; Dale, N. J.
ABSTRACT: Studies in infants and young children with congenital visual impairment (VI) have indicated early developmental vulnerabilities, conversely research with older children and adults have highlighted areas of cognitive strength. A minimal amount is known, however, about the possible combination of strengths and weaknesses in adolescence, and this present study therefore aims to explore the neuropsychological presentation and adaptive behavior profile in high-functioning adolescents with congenital VI. Participants completed a battery of commonly used neuropsychological measures assessing memory, executive function, and attention. The measures utilized focused on auditory neuropsychological function, because only subtests that could be completed with auditory administration were suitable for this sample. Parents completed standardized measures of adaptive behavior, executive function, and social communication. Compared to aged-based norms for normal sight, adolescents with VI demonstrated strengths in aspects of working memory and verbal memory. Furthermore, performance across the neuropsychological battery was within or above the average range for the majority of the sample. In contrast, parent-report measures indicated areas of weakness in adaptive functioning, social communication, and behavioral executive functioning. Overall, this study provides preliminary evidence that relative to fully sighted peers, high-functioning adolescents with VI present with an uneven profile of cognitive and adaptive skills, which has important implications for assessment and intervention.